In the Kingdom of Men: Love, Faith and Spirituality in von Trier's Breaking the Waves - Fernandez, Ingrid (The journal of religion and film, 2011)
Rehabilitating Lars von Trier: The power of von Trier’s Breaking the Waves lies exactly in its irreducibility to a fixed interpretation. The director reconceptualizes the themes of spiritual devotion, faith and love in an unorthodox tale of the human struggle to find meaning and purpose in the world. The character of Bess allows us to penetrate into the innermost regions of the mind and affirms a humanistic approach to our relationship to ourselves and others. Von Trier places an individual’s actions as a form of development, a gesture towards transcendence that nonetheless exists within the mixture of banality and profundity that constitutes the world of man.